Β-Thymosins participate in antiviral immunity of red swamp crayfish (Procambarus clarkii). Issue 2 (August 2015) - Shi, Xiu-Zhen; Shi, Li-Jie; Zhao, Yan-Ran; Zhao, Xiao-Fan; Wang, Jin-Xing
Highlights Nine isoforms of β-thymosins were identified from crayfish Procambarus clarkii. Three to six isoforms of β-thymosins were detected in one tissue. PcThy-4 was upregulated in the crayfish challenged by WSSV. PcThy-4 promotes hemocyte phagocytosis of WSSV. PcThy-4 inhibits WSSV replication and increases the survival rate of WSSV-infected crayfish.